Special edition using Microsoft Windows Vista - Cowart, Robert (Series special edition., 2008)
SPECIAL EDITION Microsoft® Windows Vista® Second Edition The only Windows Vista book you need We crafted this book to grow with you, providing the reference material you need as you move toward Vista proficiency and use more advanced features. If you buy only one book on Vista, Special Edition Using Microsoft® Windows Vista®, Second Edition, is the book you need. Tired of the constant barrage of spam, spyware, viruses and other 'Net nasties? We show you how to rebuke the onslaught of hacker attacks, protect your identity, and keep your sanity, all at the same time. Is the new Vista interface making your trigger-finger itch? Ours too ... that is, until we turned Windows inside out, shook out all the loose parts, and figured out just what makes this beast tick. Learn from our pain and suffering. If you finally broke down and purchased a Windows Media Center computer, or if you think you have one and didn't even know it, you are holding just the book for you. We show you how to get up to speed with your new computer, transforming it from the little PC that could into the media juggernaut, entertainment center, gaming center, and way-better-than-TiVo replacement you never knew it could be. Ready to upgrade? We provide from-the-trenches advice on upgrading to Windows Vista. Maybe you to still want to run Windows XP but would like to try Vista for a while to see if you like it. We cover how to dual-boot your computer safely with both operating systems. Category: Microsoft® Windows Operating System Covers: Microsoft® Windows Vista®, all versions Windows Vista Service Pack 1 User Level: Beginner-Intermediate Robert Cowart has written more than 40 books that have sold more than 1 million copies worldwide. He made his name writing for Sybex and Osborne - most notably in the best-selling Mastering Windows series. As an author and media developer for Que, Bob has written numerous Windows titles, including multiple editions of Que's flagship Windows book, Special Edition Using Microsoft® Windows®. Brian Knittel is a software developer, consultant, and writer. He's authored or coauthored many of Que's best-selling Windows books, including Que's leading Windows book, Special Edition Using Microsoft® Windows®. Brian also is the author of Windows XP Under the Hood and coauthored Upgrading and Repairing Windows® with Scott Mueller.